Differences in treatment and survival of older patients with operable breast cancer between the United Kingdom and the Netherlands – A comparison of two national prospective longitudinal multi-centre cohort studies. (March 2022) - van der Plas-Krijgsman, Willeke G.; Morgan, Jenna L.; de Glas, Nienke A.; de Boer, Anna Z.; Martin, Charlene L.; Holmes, Geoffrey R.; Ward, Susan E.; Chater, Tim; Reed, Malcolm W.; Merkus, Jos W.S.; van Dalen, Thijs; Vulink, Annelie J.E.; et al.
Abstract: Background: Previous studies have shown that survival outcomes for older patients with breast cancer vary substantially across Europe, with worse survival reported in the United Kingdom. It has been hypothesised that these differences in survival outcomes could be related to treatment variation. Objectives: We aimed to compare patient and tumour characteristics, treatment selection and survival outcomes between two large prospective cohorts of older patients with operable breast cancer from the United Kingdom (UK) and The Netherlands. Methods: Women diagnosed with operable breast cancer aged ≥70 years were included. A baseline comprehensive geriatric assessment was performed in both cohorts, with data collected on age, comorbidities, cognition, nutritional and functional status. Baseline tumour characteristics and treatment type were collected. Univariable and multivariable Cox regression models were used to compare overall survival between the cohorts. Results: 3262 patients from the UK Age Gap cohort and 618 patients from the Dutch Climb cohort were included, with median ages of 77.0 (IQR: 72.0–81.0) and 75.0 (IQR: 72.0–81.0) years, respectively. The cohorts were generally comparable, with slight differences in rates of comorbidity and frailty. Median follow-up for overall survival was 4.1 years (IQR 2.9–5.4) in Age Gap and 4.3 years (IQR 2.9–5.5) in Climb. In Age Gap, both the rates of primary endocrine therapy and adjuvant hormonal therapy after surgery were approximately twice those in Climb (16.6% versus 7.3%, p < 0.001 for primary endocrine therapy, and 62.2% versus 38.8%, p < 0.001 for adjuvant hormonal therapy). There was no evidence of a difference in overall survival between the cohorts (adjusted HR 0.94, 95% CI 0.74–1.17, p = 0.568). Conclusions: In contrast to previous studies, this comparison of two large national prospective longitudinal multi-centre cohort studies demonstrated comparable survival outcomes between older patients with breast cancer treated in the UK and The Netherlands, despite differences in treatment allocation. Highlights: No survival difference between UK and Netherlands for older breast cancer patients. Similar patient and tumour characteristics seen in both cohorts. Higher rates of mastectomy for older breast cancer patients in Netherlands. Higher rates of adjuvant therapies for older breast cancer patients in UK.